Policy pathways and barriers: examining the effects on SME growth in Australasia - Abayomi K. Akinboye; Sussie Celna Morrish; Jamie D. Collins (Humanities & Social Sciences Communications)
Abstract Entrepreneurial venture growth is viewed as crucial to economic growth and development and is aggressively promoted by governments, often accompanied by strong policies. Despite the availability of resources and assistance, many small businesses stay small and do not grow. Over many decades, entrepreneurship scholars have examined this phenomenon, acknowledging its peculiarity in many developing countries. However, there has been no detailed investigation into why this is so in developed economies. This study examines obstacles to SME growth in a study of 307 Small and Medium Enterprises in Australasia. The study finds that, among other factors that inhibit venture growth, the unwillingness of owners to grow is very significant, and these findings have implications for theory and practice.